Hydrogen Production: Amorphous Ruthenium‐Sulfide with Isolated Catalytic Sites for Pt‐Like Electrocatalytic Hydrogen Production Over Whole pH Range (Small 46/2019). Issue 46 (13th November 2019) - Li, Pengsong; Duan, Xinxuan; Wang, Shiyuan; Zheng, Lirong; Li, Yaping; Duan, Haohong; Kuang, Yun; Sun, Xiaoming
Abstract : In article number 1904043, Haohong Duan, Yun Kuang, Xiaoming Sun, and co‐workers use ruthenium, a much cheaper noble metal (the price is about 1/3 of Pt metal) with Pt like adsorption energy to H, to synthesize amorphous RuS x nanoparticles with atomically isolated active sites adhered on the surface of sulfur‐doped graphene for hydrogen evolution, affording Pt‐like or even higher activity in the entire pH range, as well as much higher durability.